2012
DOI: 10.1302/0301-620x.94b2.27729
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and radiological results following radial osteotomy in patients with Kienböck’s disease

Abstract: Radial osteotomy is currently advocated for patients with Lichtman's stages II and IIIA of Kienböck's disease; its place in the treatment of patients with stage IIIB disease remains controversial. The purpose of this study was to evaluate the medium-term results of this procedure and to compare the outcome in patients with stage IIIB disease and those with earlier stages (II and IIIA). A total of 18 patients (18 osteotomies) were evaluated both clinically and radiologically at a mean follow-up of 10.3 years (4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
17
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 41 publications
2
17
0
Order By: Relevance
“…Studies with more than 10 years of follow-up on average report mean (Quick)DASH scores between 6.1 and 14 and pain scores between 0.2 and 3.0 after radial shortening osteotomy (►Table 4). [21][22][23][24][25] Luegmair et al found that patients had poorer physical function when the dominant side was affected. 25 We found no such difference by hand dominance.…”
Section: Discussionmentioning
confidence: 99%
“…Studies with more than 10 years of follow-up on average report mean (Quick)DASH scores between 6.1 and 14 and pain scores between 0.2 and 3.0 after radial shortening osteotomy (►Table 4). [21][22][23][24][25] Luegmair et al found that patients had poorer physical function when the dominant side was affected. 25 We found no such difference by hand dominance.…”
Section: Discussionmentioning
confidence: 99%
“…The only documented difference between radial shortening and ulnar lengthening is that the latter is associated with higher rates of nonunion. 2 To avoid the complications and technical pitfalls of radial shortening osteotomy in addition to inappropriateness for patients with positive ulnar variance, Almquist 3 in 1986 described an alternative procedure to reduce lunate pressure: a capitate-shortening osteotomy associated with capitate-hamate fusion (CSCHF).…”
mentioning
confidence: 99%
“…2 This became a dogma for most hand surgeons 15 despite the good clinical results published by many authors with radial osteotomies in advanced Kienbock's disease. [16][17][18][19][20][21][22][23]…”
mentioning
confidence: 99%